Stride-time variability is related to sensorimotor cortical activation during forward and backward walking. (23rd January 2019) - Groff, Boman R.; Antonellis, Prokopios; Schmid, Kendra K.; Knarr, Brian A.; Stergiou, Nicholas
Highlights: Changes in stride-time variability corresponded with changes in hemodynamic activity in the motor cortex during walking. Hemodynamic response and stride-time variability did not differ between forward and backward treadmill walking conditions. Body movement and relative head movement during walking did not suggest that motion contamination confounded fNIRS results. Abstract: Previous research has used functional near-infrared spectroscopy (fNIRS) to show that motor areas of the cortex are activated more while walking backward compared to walking forward. It is also known that head movement creates motion artifacts in fNIRS data. The aim of this study was to investigate cortical activation during forward and backward walking, while also measuring head movement. We hypothesized that greater activation in motor areas while walking backward would be concurrent with increased head movement. Participants performed forward and backward walking on a treadmill. Participants wore motion capture markers on their head to quantify head movement and pressure sensors on their feet to calculate stride-time. fNIRS was placed over motor areas of the cortex to measure cortical activation. Measurements were compared for forward and backward walking conditions. No significant differences in body movement or head movement were observed between forward and backward walking conditions, suggesting that conditional differences in movement did not influence fNIRS results. Stride-time was significantly shorter during backward walking than during forward walking, but not more variable. There were no differences in activation for motor areas of the cortex when outliers were removed. However, there was a positive correlation between stride-time variability and activation in the primary motor cortex. This positive correlation between motor cortex activation and stride-time variability suggests that forward walking variability may be represented in the primary motor cortex.